Silicon nitride green sheet and its manufacturing method

A silicon nitride green sheet with controlled particle size distribution and filling rate addresses defects in silicon nitride sintered bodies, achieving high thermal conductivity and reduced defects through uniform bonding and void management.

JP7615652B2Active Publication Date: 2025-01-17PROTERIAL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020207361
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-15
Publication Date
2025-01-17
Estimated Expiration
2040-12-15

AI Technical Summary

Technical Problem

Existing methods for producing silicon nitride sintered bodies face challenges in achieving high thermal conductivity while minimizing defects such as warping, cracking, and poor molding accuracy due to issues with voids, particle size distribution, and volumetric expansion during nitriding reactions.

Method used

A silicon nitride green sheet is formulated with controlled particle size distribution and a filling rate between 59% to 80% volume fraction, using silicon and a sintering aid, to facilitate uniform bonding and accommodate volumetric expansion during nitriding reactions, thereby reducing defects and enhancing thermal conductivity.

Benefits of technology

The method produces a silicon nitride sintered body with high thermal conductivity and minimal defects, such as warping and cracking, by ensuring a balanced particle distribution and void space, resulting in improved molding accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615652000003
    Figure 0007615652000003
  • Figure 0007615652000004
    Figure 0007615652000004
  • Figure 0007615652000001
    Figure 0007615652000001
Patent Text Reader

Abstract

To provide a green sheet of silicon nitride for obtaining a sintered body of silicon nitride which exhibits a high thermal conductivity with little appearance defect and poor molding accuracy, and to provide a production method for the same.SOLUTION: A green sheet of silicon nitride is used as a precursor of a sintered body of silicon nitride, and is a sheet containing silicon and a sintering aid. When particle diameters corresponding to the volume fractions of 10%, 50% and 90% in the volume-based integrated particle diameter distribution of silicon are D10, D50 and D90, D10 / D90 is greater than 0 and 0.15 or less, D50 / D90 is 0.4 or less, and a filling ratio occupied by silicon is 59 volume% or more and 80 volume% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a silicon nitride green sheet containing silicon and a sintering aid, which is used as a precursor of a silicon nitride sintered body, and a method for producing the same. [Background technology]

[0002] Silicon nitride (Si3N4) has excellent mechanical properties such as high-temperature strength and abrasion resistance, as well as heat resistance, low thermal expansion, thermal shock resistance, and corrosion resistance against metals such as Al and Ag. For this reason, silicon nitride sintered bodies are used as structural materials for gas turbines, engines, steelmaking machinery, etc., and as materials resistant to molten metal wear. In addition, due to its excellent electrical insulation properties, it is used as an electronic component material for circuit boards, etc., and as an electrical insulating material.

[0003] In recent years, semiconductor elements that generate a large amount of heat, such as high-frequency transistors and power semiconductors, have become increasingly popular. Materials for semiconductor elements that generate a large amount of heat are required to have not only electrical insulation but also excellent heat dissipation properties, so there is a growing demand for ceramic substrates that exhibit high resistivity and high thermal conductivity. Traditionally, aluminum nitride (AlN) has been widely used as a material for ceramic substrates.

[0004] Aluminum nitride has excellent electrical insulation and thermal conductivity, but low mechanical strength and fracture toughness. When assembling a circuit board unit, aluminum nitride substrates are prone to cracking when fastened. Furthermore, because aluminum nitride has a significantly different thermal expansion coefficient from silicon, mounting silicon semiconductor elements on aluminum nitride substrates can easily result in cracks or breakage due to thermal expansion and contraction.

[0005] Currently, silicon nitride substrates are being used in place of aluminum nitride substrates, which have issues with mounting reliability. Silicon nitride substrates are sintered bodies of silicon nitride, and are formed from sintered silicon nitride and grain boundary phases derived from sintering additives. Although silicon nitride has a lower thermal conductivity than aluminum nitride, its thermal expansion coefficient is close to that of silicon, and it forms sintered bodies with excellent mechanical strength, fracture toughness, and thermal fatigue resistance.

[0006] Silicon nitride has a stable crystalline structure that is strongly bonded by covalent bonds, giving it excellent heat resistance and high hardness. There are two main crystalline structures of silicon nitride: α-type and β-type. α-type is a low-temperature phase of the trigonal crystal system that exists at temperatures lower than around 1400°C. β-type is a high-temperature phase of the hexagonal crystal system that is formed by a phase transition from α-type at temperatures between 1400°C and 1600°C.

[0007] A known method for producing a silicon nitride sintered body is to sinter silicon nitride powder in a nitrogen gas atmosphere with the addition of a sintering aid. Silicon nitride is a non-oxide, has strong covalent bonds, and is difficult to sinter densely. For this reason, sintering aids such as aluminum oxide, yttrium oxide, and magnesium oxide are added during heat treatment.

[0008] Alpha silicon nitride powder is primarily used as the raw material for self-sintering sintered bodies. Alpha silicon nitride undergoes a phase transition to the columnar crystal beta silicon nitride, improving the mechanical properties of the sintered body. Self-sintering sintered bodies are generally known to have excellent mechanical strength, including bending strength. Self-sintering sintered bodies have been obtained with thermal conductivity approaching 100 W / (m·K).

[0009] Another known method for producing silicon nitride sintered bodies is reactive sintering and post-sintering of silicon powder in a nitrogen gas atmosphere. While reactive sintering is expected to yield higher thermal conductivity, it also undergoes volumetric changes due to the silicon nitriding reaction. During reactive sintering, volumetric expansion due to the nitriding reaction and volumetric contraction due to sintering occur, making it difficult to mold the body into a near-net shape. Measures are also required to prevent deformations such as warping, cracks, and breakage. Near-net shape refers to a finished body with dimensions and shape close to those of the final product, eliminating the need for secondary processing.

[0010] Patent Document 1 describes a silicon nitride sintered body produced by reaction sintering. This sintered body is produced by heating a raw material containing a mixed metal silicon material consisting of 80% to 95% by weight of coarse metal silicon powder with an average particle size of 10 μm to 30 μm and 5% to 20% by weight of fine metal silicon powder with an average particle size of 1 μm to 10 μm to a temperature of 1390°C to 1500°C in a nitrogen atmosphere.

[0011] Patent Document 2 describes a silicon nitride sintered body produced by self-sintering using atmospheric sintering or gas pressure sintering. 2 / g or more 20m 2 / g or less, the proportion of β-type silicon nitride is 70 mass% or more, D50 is 0.5 μm or more and 3 μm or less, D90 is 3 μm or more and 6 μm or less, the iron content is 200 ppm or less, the aluminum content is 200 ppm or less, the total content of metal impurities other than iron and aluminum is 200 ppm or less, and the crystallite diameter D of the β-type silicon nitride is C is 60 nm or more, and the specific surface area equivalent diameter D BET and crystallite diameter D C Relative to D BET / D C (nm / nm) is 3 or less, and the crystal strain of β-type silicon nitride is 1.5 × 10 -4 The following silicon nitride powders have been used:

[0012] Patent Document 3 describes a silicon nitride sintered body produced by self-sintering. This sintered body has silicon nitride particles and a grain boundary phase containing Mg and at least one rare earth element, and the ratio (RExOy / MgO) of Mg and rare earth element (RE) converted into their oxides is in the range of 0.05 to 5. The silicon nitride particles present in an arbitrarily set 20×20 μm area on the processed surface have an average major axis length L of 5.0 μm or less, an average ratio (L / S) of the major axis length L to the minor axis length S of 5.0 μm or less, and an area of ​​each particle in an arbitrarily set 300×300 μm area on the processed surface is 0.01 μm or less. 2 The pores described above account for 0.01% to 5% of the total area, the average distance between the centers of gravity of the most adjacent pores among the pores is 5 μm or more, and the coefficient of variation of the distance between the centers of gravity is 1.5 or less. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Japanese Patent Application Publication No. 7-309669 [Patent Document 2] International Publication No. 2018 / 110564 [Patent Document 3] Japanese Patent Application Laid-Open No. 2014-073945 Summary of the Invention [Problem to be solved by the invention]

[0014] Reaction sintering is a promising method for producing silicon nitride sintered bodies from the perspective of obtaining high thermal conductivity and fracture toughness. To obtain higher thermal conductivity in a reaction sintering manufacturing process, it is important to reduce the voids in the sintered body and increase the silicon nitride filling rate. However, there is room for improvement in conventional technology regarding increasing the filling rate.

[0015] The raw material used in Patent Document 1 is a mixture of two types of metal silicon powders with a two-particle distribution, so the difference in particle size between the coarse powder and the fine powder may be small, or the particle size frequency distribution may have an extremely two-peak shape. In such cases, the silicon may not be well packed, voids of a certain size or larger may be easily formed, or the size and distribution of the voids may vary widely, which may increase the impact of volume expansion associated with the nitriding reaction.

[0016] Furthermore, in the case of self-sintering as in Patent Documents 2 and 3, glass phases, grain boundaries, and voids are likely to form, which poses many obstacles to improving thermal conductivity. Generally, increasing the amount of sintering aids added is considered a method for increasing the packing density of a sintered body. However, increasing the amount of sintering aids increases the amount of glass phases with low thermal conductivity in the sintered body, which may actually lower the thermal conductivity of the sintered body.

[0017] Another problem with reactive sintering manufacturing processes is that the filling rate before the nitriding reaction is too high. The silicon that constitutes the precursor for reactive sintering expands in volume during the nitriding reaction. Therefore, if the silicon filling rate in the precursor is too high, the volume expansion associated with the nitriding reaction causes large deformation and excessive stress, resulting in poor appearance such as warpage, cracks, breakage, and poor molding accuracy.

[0018] In particular, when the silicon filling rate in the precursor is about 82% by volume or more, the volume expansion exceeds the volume of the voids, resulting in significant defects and failures. In Patent Document 1, reactive sintering is performed, but the filling rate and porosity of the precursor are not clear, and the problem of volume expansion is not fully considered.

[0019] Therefore, an object of the present invention is to provide a green sheet for silicon nitride that can produce a silicon nitride sintered body that exhibits high thermal conductivity with little appearance or molding precision defects, and a method for producing the same. [Means for solving the problem]

[0020] In order to solve the above problems, the silicon nitride green sheet of the present invention is used as a precursor for a silicon nitride sintered body and contains silicon and a sintering aid, and when the particle sizes corresponding to 10%, 50% and 90% volume fractions in the volume-based cumulative particle size distribution of the silicon are defined as D10, D50 and D90, respectively, the ratio of D10 to D90 (D10 / D90) is greater than 0 and not more than 0.15 and the ratio of D50 to D90 (D50 / D90) is not more than 0.4, and the filling factor of the silicon is 59% by volume or more and 80% by volume or less.

[0021] Furthermore, the present invention provides a method for producing a silicon nitride green sheet, which is used as a precursor for a silicon nitride sintered body and contains silicon and a sintering aid. The method comprises the steps of: preparing powdered silicon such that the ratio of D10 to D90 (D10 / D90) is greater than 0 and not greater than 0.15 and the ratio of D50 to D90 (D50 / D90) is not greater than 0.4, where D10, D50, and D90 are the particle sizes corresponding to 10%, 50%, and 90% of the volume fraction in the volume-based cumulative particle size distribution of the silicon, respectively; mixing the silicon and the sintering aid in a dispersion medium to prepare a slurry; applying the slurry to a substrate; and drying the applied slurry, to obtain a silicon nitride green sheet having a silicon filling rate of 59% to 80% by volume after drying. [Effects of the Invention]

[0022] According to the present invention, it is possible to provide a silicon nitride green sheet that can produce a silicon nitride sintered body that exhibits high thermal conductivity with little appearance or molding precision defects, and a method for producing the same. [Brief explanation of the drawings]

[0023] [Figure 1] FIG. 1 is a flow diagram showing a method for manufacturing a silicon nitride green sheet according to an embodiment of the present invention. [Figure 2]FIG. 1 is a diagram showing the relationship between the particle size and the filling rate of silicon in a silicon nitride green sheet. DETAILED DESCRIPTION OF THE INVENTION

[0024] Hereinafter, a silicon nitride green sheet according to one embodiment of the present invention and a method for producing the same will be described with reference to the drawings.

[0025] The silicon nitride green sheet according to this embodiment is used as a precursor for producing a silicon nitride sintered body by reactive sintering. The silicon nitride green sheet contains powdered silicon (Si) and a sintering aid, and may contain a binder as needed.

[0026] Silicon nitride sintered bodies are obtained by reactive sintering of molded powdered silicon together with a sintering aid in a nitrogen gas atmosphere. When silicon (Si) is heat-treated at high temperatures of around 1300°C or higher in a nitrogen gas atmosphere, it undergoes a nitriding reaction to become silicon nitride (Si3N4). The silicon nitride particles sinter together to obtain a silicon nitride sintered body.

[0027] In this specification, the term "silicon nitride green sheet" refers to a sheet-like compact composed of powdered silicon and a sintering aid, and refers to a precursor before the silicon undergoes a nitriding reaction. The silicon nitride green sheet is in the form of a sheet whose thickness is small compared to its width and length, but the width, length, and thickness of the sheet are not particularly limited.

[0028] The silicon nitride green sheet according to this embodiment has a silicon filling rate of 59% to 80% by volume, with the remainder of the sheet being mainly composed of a small amount of sintering aid, a small amount of binder, and voids.

[0029] When silicon particles are converted into silicon nitride through a nitriding reaction, the volume calculated from the unit cell expands by approximately 1.22 times. By setting the silicon filling rate in the sheet to between 59 and 80 volume percent, the filling rate of silicon nitride after the nitriding reaction can be increased, resulting in the desirable effects described below.

[0030] In order to obtain high thermal conductivity, it is preferable for silicon nitride sintered bodies to have a high silicon nitride filling rate. Therefore, it is also preferable for the silicon nitride green sheet, which is the precursor of the sintered body, to have a high silicon filling rate. According to calculations using a filling model, if the silicon particle filling rate is 59% by volume or more, the silicon nitride particles will be more likely to bond during the nitriding and sintering reactions. As a result, it is possible to obtain high thermal conductivity.

[0031] If the silicon filling rate in the silicon nitride green sheet is higher than 80% by volume, the silicon nitride filling rate after the nitriding reaction approaches 100% by volume, leaving insufficient space for the volume expansion that accompanies the nitriding reaction. In such cases, the volume expansion exceeds the volume contraction caused by sintering, and particle rearrangement is restricted, resulting in significant deformation and stress in the sintered body. In contrast, if a void content of approximately 2% by volume or more is maintained, the volume expansion and rearrangement of particles are permitted, even if volume expansion occurs during the nitriding reaction, and deformation and stress can be alleviated.

[0032] The filling rate of silicon in the green sheet is at least 59% by volume or more, but from the viewpoint of increasing the thermal conductivity of the sintered body, it is preferably 65% ​​by volume or more, more preferably 70% by volume or more, and even more preferably 75% by volume or more. Also, it is at least 80% by volume or less, but can be 75% by volume or less, 70% by volume or less, 65% by volume or less, etc., depending on the application and required performance of the sintered body.

[0033] Defects and defects that occur in sintered bodies are caused by volume expansion associated with the nitriding reaction, thermal expansion due to heating during heat treatment, and thermal contraction due to cooling after heat treatment. Specific examples of defects and defects include cracks, breakage, and poor appearance such as warping that can be problematic in applications such as printed circuit boards, as well as poor molding accuracy when molding to near-net shapes or target dimensions. These defects and defects can be reduced by lowering the silicon filling rate and ensuring voids in the sintered body.

[0034] In the silicon nitride green sheet of this embodiment, when the particle sizes corresponding to 10%, 50% and 90% cumulative undersieve volume fractions in the volume-based cumulative particle size distribution of silicon are defined as D10, D50 and D90, respectively, the ratio of D10 to D90 (D10 / D90) is greater than 0 and not more than 0.15, and the ratio of D50 to D90 (D50 / D90) is not more than 0.4.

[0035] When the D50 / D90 ratio is 0.4 or less, the small particles (particles of D10 or less) and medium particles (particles of D10 or more and D50 or less), which account for 50% by volume of the silicon powder in the sheet, are sufficiently smaller than the large particles (particles of D90 or more), which account for 10% by volume of the sheet, and therefore a large amount of small and medium particles can be filled into the gaps between the large particles.

[0036] Furthermore, when the D10 / D90 ratio is 0.15 or less, the small particles (particles of D10 or less), which account for 10% by volume of the silicon powder in the sheet, are sufficiently smaller than the large particles (particles of D90 or more), which account for 10% by volume of the total, and the medium particles (particles of D10 or more and D50 or less), which account for 40% by volume of the total, and therefore a large amount of small particles can be filled into the gaps between the large and medium particles.

[0037] Therefore, using silicon that satisfies the D10 / D90 and D50 / D90 conditions allows a sufficient number of medium particles to be closely arranged around the large particles, and a sufficient number of small particles to be closely arranged around the medium particles. Furthermore, the D50 / D90 condition reduces the size of voids and increases the uniformity of their size and distribution, ensuring dispersed space for volume expansion, making the green sheet less susceptible to volume expansion associated with the nitriding reaction. Therefore, using silicon that satisfies these conditions allows for uniform particle bonding during nitriding and sintering, and a silicon filling rate in the range of 59% to 80% by volume, resulting in a silicon nitride green sheet that is less susceptible to deformation and stress during reaction sintering.

[0038] D10 / D90 is preferably 0.01 or more, more preferably 0.03 or more. When D10 / D90 is 0.03 or more, the proportion of silicon with extremely small particle diameter is low, and the surface area of ​​the powder as a whole is small, so the amount of binder used can be reduced. D50 / D90 is greater than D10 / D90 of the powder and is 0.4 or less.

[0039] The D50 of the silicon powder in the silicon nitride green sheet is preferably 0.5 μm or more and 20 μm or less. If D50 is less than 0.5 μm, the amount of binder relative to the total specific surface area of ​​the powder is small, resulting in a low mechanical strength of the sheet. If D50 exceeds 20 μm, the surface of the silicon nitride green sheet becomes uneven and the nitriding reaction rate slows. In contrast, if D50 is 0.5 μm or more and 20 μm or less, the surface of the silicon nitride green sheet can be smoothed while the nitriding reaction rate can be increased.

[0040] The D50 of the silicon powder in the silicon nitride green sheet is preferably 0.8 μm or more from the viewpoint of obtaining high strength while suppressing the amount of binder. Furthermore, from the viewpoint of smoothing the surface of the silicon nitride green sheet and accelerating the nitriding reaction rate, it is preferably 10 μm or less, more preferably 4 μm or less, and even more preferably 3 μm or less. At 4 μm or less, sufficient smoothness is obtained, enabling the nitriding reaction time to be shortened. At 0.8 μm or more and 3 μm or less, high strength can be obtained with a small amount of binder, and a surface with minimal irregularities can also be obtained. At 0.8 μm or more and 2 μm or less, in addition to high strength and smoothness, a higher filling rate can be obtained.

[0041] The particle size and particle size distribution of silicon can be measured using a laser diffraction / scattering particle size distribution measuring device. The particle size and particle size distribution of silicon in a silicon nitride green sheet can be determined by dissolving the silicon nitride green sheet in a solvent such as alcohol, drying it to remove the solvent, and separating and measuring the silicon in the resulting powder based on specific gravity, or by observing any cross section of the silicon nitride green sheet with an electron microscope to collect data such as the circle-equivalent diameter of the silicon particles.

[0042] The porosity of silicon nitride green sheets can be determined by observation with a scanning electron microscope (SEM). An arbitrary cross section of the silicon nitride green sheet is cut out, and the cross section is photographed with an SEM to obtain an SEM image. The SEM image is then processed using binarization or ternarization, and the area ratio of voids per unit area is calculated, assuming that low-density areas in the image are voids where there is no silicon or sintering aid. SEM images are taken at a magnification of between 500x and 1000x, for multiple cross sections and microscope fields.

[0043] The number of cross sections taken for SEM images is preferably two or more, and more preferably five or more, to minimize variation due to measurement error. The average void area ratio is calculated based on a large number of SEM images, and when the variation in the average value becomes sufficiently small as the number of images increases, the average area ratio is taken as the void ratio of the silicon nitride green sheet. When the sheet contains only small amounts of sintering aids and binders, the silicon filling ratio [%] can be considered to be 100 - void ratio [%].

[0044] As the sintering aid, it is preferable to use a compound containing one or more elements selected from the group consisting of magnesium (Mg), yttrium (Y), and rare earth elements (RE). Examples of compounds containing these elements include oxides, nitrides, and silicides. The sintering aid may contain one or more of these elements.

[0045] Examples of rare earth elements include lanthanides, such as lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).

[0046] Mg, Y, and rare earth elements have low solid solubility in silicon nitride and are unlikely to change the crystal structure or chemical composition, making them effective in increasing the thermal conductivity of silicon nitride itself. Mg and Y are particularly effective in densifying the sintered body to achieve high thermal conductivity. Preferred compounds containing Mg and Y include magnesium oxide (MgO) and yttrium oxide (YO).

[0047] As the rare earth element, one or more elements selected from the group consisting of La, Ce, Gd, Dy, and Yb are particularly preferred. Sintering aids containing these elements can promote sintering while suppressing the temperature and pressure, thereby reducing the cost of heat treatment.

[0048] When the composition of the sintering aid contains La, Y, Gd or Yb, and Mg, the mixed weight of the rare earth elements converted into oxides is x O y , when the mixed weight of magnesium oxide is MgO, RE x O y It is preferable that the weight ratio of these rare earth elements to Mg is 1. If the weight ratio of these rare earth elements to Mg is large, fine particles derived from the sintering aid are more likely to be formed during heat treatment. This is because these rare earth elements are less likely to dissolve in silicon nitride than Mg.

[0049] The amount of sintering aid, calculated as oxide, is preferably 1% by mass or more, more preferably 2% by mass or more, based on 100% by mass of the total of silicon and sintering aid. It is also preferably 15% by mass or less, more preferably 10% by mass or less. This amount can promote sintering of silicon nitride and high purity within the particles, while suppressing the formation of a glass phase with low thermal conductivity.

[0050] The thickness of the silicon nitride green sheet is preferably 0.1 mm or more and 1 mm or less, and more preferably 0.1 mm or more and 0.5 mm or less. With such a thickness, a thin silicon nitride sintered body can be produced. A silicon nitride green sheet of such a thickness can be obtained by pressing after drying during the manufacturing process, or it can be obtained without pressing after drying. Reducing the thickness to 0.5 mm or less by pressing, etc., can achieve higher thermal conductivity.

[0051] The silicon nitride green sheet described above uses silicon that satisfies the D10 / D90 and D50 / D90 requirements, resulting in a silicon filling rate of 59% to 80% by volume, providing a precursor with dispersed spaces for volume expansion during the nitriding reaction. It is possible to achieve a high filling rate of nearly 80% by volume even at the precursor stage of the silicon nitride sintered body. Furthermore, the nitriding reaction and sintering facilitate uniform particle bonding, resulting in a dense silicon nitride sintered body. Therefore, when used in a reactive sintering manufacturing process, silicon nitride sintered bodies exhibit high thermal conductivity and are less prone to appearance defects such as warping, cracks, breakage, or molding precision defects.

[0052] Next, a method for manufacturing the silicon nitride green sheet having a silicon filling rate within a predetermined range will be described. In the following description, a manufacturing method in which raw material powders are wet-mixed and finally dried will be exemplified together with a heat treatment method.

[0053] FIG. 1 is a flow diagram showing a method for producing a silicon nitride green sheet according to an embodiment of the present invention. 1, the method for producing a silicon nitride green sheet according to this embodiment includes a particle size adjusting step S10, a mixing step S20, a coating step S30, and a drying step S40. Through these steps, a silicon nitride green sheet having a silicon filling rate of 59% to 80% by volume can be obtained, which serves as a precursor for a silicon nitride sintered body.

[0054] The silicon nitride sintered body is obtained as a silicon nitride substrate, which is a plate-shaped sintered body, by using the silicon nitride green sheet as a precursor and passing through a heat treatment step S50. The silicon nitride substrate can be used for applications such as printed circuit boards.

[0055] In the particle size adjusting step S10, the particle size distribution of the powdered silicon used as the raw material for the silicon nitride green sheet is adjusted so that the filling rate of silicon in the silicon nitride green sheet falls within a predetermined range. The particle size distribution can be adjusted by mixing the powders together so that D10 / D90 is greater than 0 and not more than 0.15, and D50 / D90 is not more than 0.4.

[0056] It is preferable to use multiple types of classified silicon powders with different median diameters (D50) and mode diameters as the silicon powders to be mixed together. The powdered silicon used as the raw material for the silicon nitride green sheet is preferably adjusted to have a D50 of 0.5 μm or more and 20 μm or less.

[0057] For example, a method can be used in which 100% by weight of large particle powder with a median diameter of 0.5 μm to 20 μm is combined with 10% by weight to 50% by weight of small particle powder with a median diameter of approximately 0.15 to 0.4 times that of the large particles, or a method can be used in which 100% by weight of large particle powder with a median diameter of 0.5 μm to 20 μm is combined with 40% by weight to 100% by weight of medium particle powder with a mode diameter of approximately 0.4 times or less and 10% by weight to 100% by weight of small particle powder with a mode diameter of approximately 0.15 times or less.

[0058] In the mixing step S20, powdered silicon and a sintering aid are mixed in a dispersion medium to prepare a slurry. Silicon and a sintering aid with controlled particle size distribution are weighed to a predetermined mixing ratio, and a binder or dispersant is added as needed, followed by wet mixing in the dispersion medium. Wet mixing suppresses the inclusion of gas components without significantly affecting the particle size distribution, and achieves the dispersion of powder and the dissociation of agglomerated particles.

[0059] From the viewpoint of dispersibility in silicon, it is preferable to use a powder of sintering aid having a particle size smaller than the D50 of silicon.

[0060] As the binder, any suitable type can be used, such as acrylic resins such as polyacrylic acid and polyacrylic acid ester, cellulose resins such as methyl cellulose and ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, etc., as long as they can be thermally decomposed at low temperatures and do not leave behind a large amount of ash, carbon, etc. Use of a binder can prevent particles from falling off from the silicon nitride green sheet after molding, making the sheet easier to handle.

[0061] Any suitable dispersion medium can be used as long as it volatilizes at low temperatures and dissolves the binder added as needed. When using a water-soluble binder such as polyacrylic acid, lower alcohols such as methanol, ethanol, and butanol can be used. Furthermore, organic solvents such as hexane, trichloroethylene, and dichloromethane, as well as water, can be used as long as they do not react excessively with the silicon or binder.

[0062] The raw materials can be mixed using an appropriate mixer such as a V-type mixer, W-type mixer, Henschel mixer, ribbon mixer, screw mixer, ball mill, bead mill, planetary mixer, high-pressure homogenizer, ultrasonic homogenizer, or roll mill.

[0063] In the coating step S30, the slurry is applied to a substrate to form a coating film containing powdered silicon, a sintering aid, a binder added as needed, and a dispersion medium. The thickness of the coating film can be adjusted appropriately depending on the application and required performance of the sintered body. However, from the viewpoint of reducing the surface irregularities and in-plane thickness variations of the sintered body, a thickness of 0.1 mm to 1 mm after drying is preferred.

[0064] As the substrate, any suitable type of material can be used, such as a resin film, resin plate, metal plate, ceramic plate, or glass plate, as long as it has a heat resistance temperature sufficiently high relative to the vaporization temperature of the dispersion medium. Resin films are particularly preferred as the substrate because they can be wound into a roll as a carrier tape. Specific examples of resin films include polyethylene terephthalate, polyethylene naphthalate, and polycarbonate.

[0065] The slurry can be applied using an appropriate coating device such as a sheet forming applicator equipped with a doctor blade or the like, a slot die coater, a knife coater, a bar coater, a gravure coater, a spray coater, etc. As the coating device, any of a roll coater, a sheet-fed coater, etc. may be used, or a device for a casting method or an extrusion molding method may be used.

[0066] In the drying step S40, the slurry coated on the substrate is dried to form a silicon nitride green sheet. The substrate with the slurry coating formed thereon is placed in a heating and drying furnace or the like, and the coating is dried to remove the dispersion medium, leaving powdered silicon and sintering aid, along with a binder added as needed, on the substrate, yielding a silicon nitride green sheet in which the powder particles are bonded together.

[0067] The drying temperature and drying time can be set as appropriate depending on the volatilization temperature of the dispersion medium, as long as the material is not altered. The silicon nitride green sheet obtained after drying may or may not be peeled from the substrate before heat treatment. Furthermore, processing such as cutting or punching may be performed before heat treatment.

[0068] After drying, the silicon nitride green sheet can be subjected to a pressure treatment to adjust the silicon filling rate, porosity, or sheet thickness. By controlling the silicon particle size distribution, it is possible to achieve a silicon filling rate of 59 volume % or more in the sheet. However, to increase the silicon filling rate or adjust the sheet thickness, the silicon can be compacted by compression using a pressure treatment. The pressure treatment can be carried out using an appropriate pressure device such as an axial press or a roll press.

[0069] In the heat treatment step S50, the silicon nitride green sheet is heat treated in a nitrogen gas atmosphere. During high-temperature heat treatment, silicon and nitrogen gas gradually react to produce silicon nitride, and the silicon nitride particles are sintered together to produce a silicon nitride substrate. The sintering aid melts and volatilizes during the heat treatment, forming a liquid phase or other interface that serves as a reaction site on the silicon surface, and after the heat treatment, a grain boundary phase containing components derived from the sintering aid is formed in the structure.

[0070] The heat treatment temperature and heat treatment time can be set as appropriate depending on the average particle size of silicon, the type of sintering aid, the mixing ratio of silicon and sintering aid, etc. When a binder is contained, a low-temperature heat treatment for debinding can be performed before the heat treatment for reactive sintering by nitriding reaction.

[0071] A preferred heat treatment method is a multi-stage heat treatment including a heat treatment for reactive sintering by a nitriding reaction and a heat treatment for promoting sintering of silicon nitride particles together. The reactive sintering can be carried out in a nitrogen gas atmosphere, for example, at a temperature of 1300°C to 1600°C. The sintering of silicon nitride particles can be carried out in a nitrogen gas atmosphere, for example, at a temperature of 1720°C to 2000°C.

[0072] These processes enable the silicon nitride sintered body to have a high silicon nitride filling rate. The remainder of the sintered body is mainly composed of a small amount of grain boundary phase containing components derived from the sintering aid, and voids. It is preferable that the silicon nitride sintered body have a high silicon nitride β fraction.

[0073] Silicon nitride substrates can be used as final products for substrate applications without secondary processing. Examples of applications for silicon nitride substrates include printed circuit boards. They are particularly suitable as materials for circuit boards for high-frequency transistors, power modules such as power semiconductors, and multi-chip modules. They can also be used as heat transfer plates for heat sinks, Peltier elements, Seebeck elements, and the like.

[0074] FIG. 2 is a diagram showing the relationship between the particle size and the packing rate of silicon in a silicon nitride green sheet. In Figure 2, the horizontal axis represents the ratio of silicon D10 to D90 (D10 / D90) and the ratio of silicon D50 to D90 (D50 / D90), and the vertical axis represents the silicon filling rate in the silicon nitride green sheet. The silicon particle size and filling rate are calculated values. It is assumed that some of the voids are filled with binder.

[0075] The triangle plots represent the D10 / D90 of silicon obtained when pressure treatment is not applied after drying. The circle plots represent the D50 / D90 of silicon obtained when pressure treatment is not applied after drying. A1 and A2, B1 and B2, and C1 and C2 are each the values ​​for the same silicon nitride green sheet. A, B, and C have different particle size distributions.

[0076] The ▲ plot shows the D10 / D90 of silicon obtained when pressure treatment is applied after drying. The ● plot shows the D50 / D90 of silicon obtained when pressure treatment is applied after drying. D1 and D2, E1 and E2, F1 and F2 are all values ​​for the same silicon nitride green sheet. DEFs have different particle size distributions.

[0077] As shown in Figure 2, the smaller the particle diameter of the silicon, the higher the silicon filling rate. One way to reduce the silicon D10 or D50 is to prepare multiple powders with different median diameters (D50) or mode diameters and add smaller particle powders. In particular, the higher the mixing ratio of powder with a small D50, the greater the change toward the smaller particle diameter side.

[0078] As the ▲ and ● plots show, when the silicon is compressed by pressure treatment after drying, the binder and small particles can be moved into the gaps between the silicon particles, resulting in a higher filling rate compared to when pressure treatment is not performed.By using pressure treatment, the filling rate of silicon in the sheet can be easily adjusted to approximately 80% by volume.

[0079] Next, specific examples of silicon nitride green sheets will be described.

[0080] (Examples 1 to 3) Examples 1 to 3 were produced using raw materials in which silicon and a sintering aid were mixed at a weight ratio of 95:5. The silicon powder used was one with a controlled particle size distribution as shown in Table 1 below, the sintering aid was Y2O3, the binder was polyacrylic acid, and the dispersion medium was butanol. The thickness of the silicon nitride green sheet was 0.5 mm. Examples 1 to 3 correspond to C to A in Figure 2, respectively.

[0081] Examples 4 to 6 Examples 4 to 6 were fabricated using raw materials consisting of silicon and a sintering aid mixed in a weight ratio of 95:5. The silicon powder used was one with a controlled particle size distribution as shown in Table 1 below, the sintering aid was a mixture of Y2O3 and MgO in a weight ratio of 2:3, the binder was polyacrylic acid, and the dispersion medium was butanol. The thickness of the silicon nitride green sheet was 0.5 mm. Examples 4 to 6 correspond to C to A in Figure 2, respectively.

[0082] (Examples 7 to 8) Examples 7 and 8 were produced using a raw material consisting of a mixture of silicon and a sintering aid in a weight ratio of 95:5. The raw material was formed into a sheet-like coating film, and then pressure treatment was performed using a roll press. The silicon powder used had a controlled particle size distribution as shown in Table 1 below. The sintering aid used was either Y2O3 alone or a mixture of Y2O3 and MgO in a weight ratio of 2:3. The binder used was polyacrylic acid, and the dispersion medium used was butanol. The thickness of the silicon nitride green sheet was 0.5 mm. Examples 7 and 8 each correspond to D in Figure 2.

[0083] (Comparative Example 1) Comparative Example 1 was produced using a raw material in which the particle size distribution of silicon in Example 1 was shifted to the larger particle size side. Conditions other than the silicon particle size were the same as in Example 1.

[0084] (Comparative Example 2) Comparative Example 2 was produced using a raw material in which the particle size distribution of silicon in Example 4 was shifted to the larger particle size side. The conditions other than the silicon particle size were the same as in Example 4.

[0085] Table 1 shows the raw material composition and manufacturing conditions for silicon nitride green sheets. Table 2 shows the particle size of the silicon powder used as raw material, the calculated D10 / D90·D10 / D50, and the calculated silicon filling rate.

[0086] [Table 1]

[0087] [Table 2]

[0088] As shown in Tables 1 and 2, in all of the systems in Examples 1 to 3 and Examples 4 to 6, which have different sintering aid compositions, the smaller the D10 / D90 or D50 / D90, the higher the silicon filling rate. Because these results are based on silicon particles converted to spherical shapes, the relative size relationship of the particle diameters is important, and it can be said that it is preferable to satisfy the above-mentioned D10 / D90 and D50 / D90 conditions depending on the particle diameter range of the silicon appropriate as a raw material.

[0089] Although the embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the present invention. For example, the present invention is not necessarily limited to those having all of the configurations of the above-described embodiments. It is possible to replace part of the configuration of an embodiment with another configuration, add part of the configuration of an embodiment to another form, or omit part of the configuration of an embodiment. [Explanation of symbols]

[0090] S10 Particle size adjustment process S20 Mixing process S30 coating process S40 Drying process S50 heat treatment process

Claims

1. A silicon nitride green sheet used as a precursor of a silicon nitride sintered body, the green sheet containing silicon, a sintering aid, and a binder, When particle sizes corresponding to 10%, 50% and 90% volume fractions in the volume-based cumulative particle size distribution of silicon are designated as D10, D50 and D90, respectively, the ratio of D10 to D90 (D10 / D90) is greater than 0 and is not greater than 0.15, and the ratio of D50 to D90 (D50 / D90) is not greater than 0.4, The filling rate of the silicon is 59% by volume or more and 80% by volume or less, A green sheet for silicon nitride having a thickness of 0.1 mm or more and 1 mm or less.

2. 2. The silicon nitride green sheet according to claim 1, The sintering aid is a compound containing one or more elements selected from the group consisting of magnesium, yttrium and rare earth elements.

3. 2. The silicon nitride green sheet according to claim 1, A green sheet for silicon nitride, wherein the amount of the sintering aid is 1 mass % or more and 15 mass % or less with respect to 100 mass % in total of the silicon and the sintering aid.

4. 2. The silicon nitride green sheet according to claim 1, The silicon nitride green sheet has a D50 of 0.5 μm or more and 20 μm or less.

5. 2. The silicon nitride green sheet according to claim 1, The silicon nitride green sheet has a D50 of 0.5 μm or more and 4 μm or less.

6. A method for producing a silicon nitride green sheet according to any one of claims 1 to 5, comprising the steps of: a step of preparing powdered silicon such that the ratio of D10 to D90 (D10 / D90) is greater than 0 and not greater than 0.15 and the ratio of D50 to D90 (D50 / D90) is not greater than 0.4, where D10, D50 and D90 are particle sizes corresponding to 10%, 50% and 90% volume fractions in a volume-based cumulative particle size distribution of the silicon, respectively; mixing the silicon and a sintering aid in a dispersion medium to prepare a slurry; applying the slurry onto a substrate; and drying the applied slurry. A method for producing a green sheet for silicon nitride, which produces a green sheet having a packing ratio of silicon of 59 volume % or more and 80 volume % or less after drying.

Citation Information

Patent Citations

  • Low heat-conductive silicon nitride sintered body by direct nitriding method having two kinds of particle distribution and its production

    JP1995309669A

  • Method for producing silicon nitride-based ceramic

    JP2011195395A

  • Silicon nitride sintered body and slide member using the same

    JP2014073945A

  • Method of manufacturing silicon nitride substrate and silicon nitride substrate

    JP2018184333A

  • Manufacturing method of sintered reaction bonded silicon nitride ceramics from silicon scrap and sintered reaction bonded silicon nitride ceramics using the same

    KR101972234B1